Preventive behaviour at work of vocational students. (3rd July 2018) - Lecours, Alexandra; Therriault, Pierre-Yves
Abstract: Background: Statistics suggest young workers are a group at high risk of sustaining injury. Vocational students are frequently included in the 'young workers' group, with all other different types of workers aged 24 or less. However, the literature exposes vocational students as having specific descriptive characteristics, suggesting that this subgroup might differ from other 'young workers'. The literature offers little description of this population towards prevention at work. The aim of the study was to explore factors associated with vocational students' preventive behaviour at work.Methods: The study was conducted with 129 participants following a predictive correlational design. Preventive behaviour and some personal, occupational and environmental factors were recorded by validated questionnaires. Multiple regression analyses were used to identify factors associated with vocational students' preventive behaviour at work.Results: Findings showed the majority of vocational students had a moderate level of preventive behaviour at work. Most relevant factors associated with preventive behaviour at work for this specific population were: (1) type of prevention training, (2) autonomous motivation, (3) study programme and (4) type of school.Conclusion: Vocational students are a specific population and it is important to work on relevant factors during their studies to help them become involved towards prevention.